Evaluation of Legume Cover Crop Species for Citrus Production in Southeast Florida - Lukas M. Hallman; John-Paul Fox; Audrey H. Beany; Alan L. Wright; Lorenzo Rossi (HortScience)
Because of the low fertility soils native to southeast Florida and the high nutrient demand of citrus trees under citrus greening—an endemic bacterial disease impacting nutrient uptake—growers are returning to the use of cover crops to improve soil fertility. Cover crops, specifically legumes, can improve soil nitrogen (N) availability because of their ability to fix N from the atmosphere. More citrus growers in southeast Florida are growing cover crops; however, there is a lack of recent research of suitable legume species and their impact on soil N cycling. To address this gap in the literature, six different treatments consisting of five legume species monocultures and one fallow plot (control) were organized into a completely randomized design. The experiment was conducted twice under warm and cool season conditions, and each treatment was replicated five times (n = 5), for a total of 30 experimental plots. Legume species were hairy indigo (Indigofera hirsuta), sunn hemp (Crotalaria juncea), cowpea (Vigna unguiculata), alfalfa (Medicago sativa), and aeschynomene (Aeschynomene americana). Biomass production, N concentration, and nodule characteristics as well as their impact on soil N were measured over a 1-year span in both warm and cool seasons. Overall, both cowpea and hairy indigo produced more biomass and, as a result, higher tissue N compared with those of the other legumes at both 60 and 150 days after planting. However, no impact on soil N was observed. Additionally, all legumes were unable to survive in the cool season, resulting in no measurable biomass at 150 days after planting. These results are relevant for citrus growers aiming to enhance soil fertility through cover crops in southeast Florida. While several legume options are available for the warm season (e.g., cowpea, hairy indigo, and sunn hemp), suitable legume species for the cool season have yet to be identified.